Spatial–temporal distribution of large-size light falling-net fisheries in the South China Sea - Qian, Jing; Li, Jiajun; Zhang, Kui; Qiu, Yongsong; Cai, Yancong; Wu, Qiaer; Tian, Han; Ma, Shengwei; Chen, Zuozhi (Frontiers in Marine Science, 2022)
With the rapid modernization of methods for monitoring fishing vessels, different ways of obtaining data on large-size light falling-net vessels have developed. In particular, the vessel monitoring system (VMS) may be used to track fishing activities in the South China Sea (SCS). In this study, we used VMS data to show the characterize and differences in the information transmitted when monitoring large-size falling-net fishing vessels, as well as their advantages and disadvantages. We investigated the spatial distribution of large-size light falling-net fisheries in the SCS using Beidou VMS data from 2017 to 2020. According to these data, vessels operate in the Nansha Islands and the waters of the Pearl River Estuary, Beibu Gulf, Zhongsha, and Xisha Islands, and there is a clear seasonal pattern of fishing in the SCS. Through the trajectories of fishing vessels from various provinces, we also compared the differences of vessels in terms of distribution areas and ports of entry and exit. Additionally, we divided the operation area of the large-size falling-net fishing vessels into four main fishing zones. The analysis compares the number of days of operation in the different fishing areas as well as seasonal variations. Our study shows that the operating area of large-size light falling-net vessels has extended southwards and that the number of days for which fishing vessels operate has increased compared with the last decade. Using the Beidou VMS to study the large-size light falling-net vessels in the SCS can provide more detailed scientific reference data for the SCS fisheries.